Citizens' perceptions of the legitimacy of independent agencies: The effects of expertise‐based and reputation‐sourced authority. - Rimkutė, Dovilė; Mazepus, Honorata (Public Administration Review)
Legitimacy is a central concern for independent agencies tasked with shaping policies. While expertise‐based and reputation‐sourced authority bases are assumed to be relevant for agency legitimacy, their individual and joint effects on citizens' perceptions lack comprehensive examination. To address this gap, the study integrates insights from bureaucratic politics, bureaucratic reputation, and cognitive psychology. Our survey experiment with Dutch citizens, focusing on the European Food Safety Authority, suggests that expertise‐based authority positively affects perceived agency legitimacy, while a negative reputation has detrimental effects. Furthermore, expertise‐based authority moderates the impact of reputation, amplifying positive effects and mitigating negative ones. This implies that agencies are more susceptible to reputational threats when they lack expertise‐based authority. The study advances the theoretical tenets of bureaucratic reputation theory and offers effective strategies for agencies to strengthen their legitimacy among the most critical audience in democratic political systems—citizens.